Improving Inventory Efficiency: A Case Study on the Application of Economic Order Quantity (EOQ) in Coffee Raw Material Management at PT. Toarco Jaya - Mangando, Yuni Putri; Mongan , Benyamin; Jaya, Amir (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to analyze and optimize the inventory control system of raw coffee bean materials at PT. Toarco Jaya Toraja Utara by applying the Economic Order Quantity (EOQ) model, along with Safety Stock and Reorder Point (ROP) calculations. The research adopts a quantitative descriptive approach using 2023 procurement and inventory data. The analysis reveals that the implementation of the EOQ method significantly reduces total inventory costs from IDR 4,395,696.33 to IDR 3,384,950.59 per year, achieving a cost efficiency of 22.99%. Moreover, the order frequency decreases from nine times to four times per year, indicating improved operational efficiency. The calculated safety stock of 225.88 kg and a reorder point of 516.30 kg further ensure inventory availability and continuity of production. These findings support the adoption of a data-driven inventory strategy, contributing to cost minimization and production reliability.